Geographic variability of hospitalizations for acute myocardial infarction in Costa Rica - Morera Salas, Melvin (2014)
This research shows the geographic pattern of hospitalizations due to acute myocardial infarction in the public health care system in Costa Rica from 2010 to 2012. For the geographical analysis we used the geographic representation of the Bayesian smoothed standardized hospitalization ratio and the areas with hospitalization rate significantly different from the national average. Spatial autocorrelation was determined by Moran's I indicator. Amplitude between variations was performed using inter percentile ratio (percentile 95/percentile 5) and the variation coefficient. The gross rate is 5.8 hospitalizations per 10 000 population in men and 2.6/10 000 in women. The range of variation between areas with higher and lower hospitalizations is more than double. The most complex national hospitals are in the metropolitan areas. We found a pattern of low rates of hospitalization for acute myocardial infarction outside of metropolitan areas. This could be related to difficulties in accessing hospital services.